2008
DOI: 10.1016/j.jfms.2008.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blood glucose concentration are associated with relatively rapid changes in circulating fructosamine concentrations in cats

Abstract: The aim of the study was to determine the time required for plasma fructosamine concentration to increase after the onset of hyperglycaemia and decrease after resolution of hyperglycaemia. Healthy cats (n=14) were infused to maintain either moderate hyperglycaemia (n=5) (actual mean glucose 17 mmol/l) or marked hyperglycaemia (n=9) (actual 29 mmol/l) for 42 days. Fructosamine exceeded the upper limit of the reference range (331 micromol/l) after 3-5 days of marked hyperglycaemia, took 20 days to plateau and, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 17 publications
(17 reference statements)
1
37
0
2
Order By: Relevance
“…In 1948, Dohan and Lukens administered large doses of glucose to normal cats and induced permanent hyperglycemia, hydropic degeneration of the islets of Langerhans, and ketonuria. It took nearly 50 years for those findings to be recognized in veterinary medicine when Link and Rand (1996) performed a similar experiment. They showed that insulin levels in healthy cats decreased within days when high blood glucose levels were maintained by glucose infusion.…”
Section: Remission Of Diabetes In Catsmentioning
confidence: 97%
See 1 more Smart Citation
“…In 1948, Dohan and Lukens administered large doses of glucose to normal cats and induced permanent hyperglycemia, hydropic degeneration of the islets of Langerhans, and ketonuria. It took nearly 50 years for those findings to be recognized in veterinary medicine when Link and Rand (1996) performed a similar experiment. They showed that insulin levels in healthy cats decreased within days when high blood glucose levels were maintained by glucose infusion.…”
Section: Remission Of Diabetes In Catsmentioning
confidence: 97%
“…They showed that insulin levels in healthy cats decreased within days when high blood glucose levels were maintained by glucose infusion. Several cats even became ketonuric and required 1 to 2 weeks of insulin therapy after cessation of the glucose infusion (Link and Rand, 1996;Link et al, 2013). The cellular mechanisms by which chronic hyperglycemia affects insulin secretion and insulin sensitivity are poorly understood.…”
Section: Remission Of Diabetes In Catsmentioning
confidence: 99%
“…O estresse crônico (superior a cinco dias) também demonstrou influência sobre os valores de frutosamina, entretanto estes animais, em média, também não apresentaram hiperglicemia, não devendo representar uma dificuldade na diferenciação de um possível DM. Este aumento da concentração sérica de frutosamina também se manteve dentro do intervalo de referência, como encontrado em estudos anteriores 4,10,12,16 .…”
Section: Discussão E Conclusõesunclassified
“…Na tentativa de se avaliar a média glicêmica para o controle do diabetes em gatos, as concentrações séricas seriadas de frutosamina trazem informações mais valiosas quando comparadas com uma única dosagem de frutosamina 4 . As frutosaminas são proteínas séricas glicadas continuamente formadas, resultantes da ligação não enzimática, irreversível e insulino-independente entre a glicose e proteínas circulantes.…”
Section: Introductionunclassified
“…Additionally, the range of fructosamine concentrations associated with a given glucose concentration was wide, with the critical difference for fructosamine being 33 µmol/l 178 . Differences in serial measurements of less than 33 µmol/l may not be indicative of fluctuations in blood glucose measurements.…”
Section: Fructosaminementioning
confidence: 99%